Root angle in maize influences nitrogen capture and is regulated by calcineurin B‐like protein (CBL)‐interacting serine/threonine‐protein kinase 15 (ZmCIPK15) - Schneider, Hannah M.; Lor, Vai Sa Nee; Hanlon, Meredith T.; Perkins, Alden; Kaeppler, Shawn M.; Borkar, Aditi N.; Bhosale, Rahul; Zhang, Xia; Rodriguez, Jonas; Bucksch, Alexander; Bennett, Malcolm J.; Brown, Kathleen M.; et al. (Plant, cell and environment, 2022)
Crops with reduced nutrient and water requirements are urgently needed in global agriculture. Root growth angle plays an important role in nutrient and water acquisition. A maize diversity panel of 481 genotypes was screened for variation in root angle employing a high‐throughput field phenotyping platform. Genome‐wide association mapping identified several single nucleotide polymorphisms (SNPs) associated with root angle, including one located in the root expressed CBL‐interacting serine/threonine‐protein kinase 15 (ZmCIPK15) gene (LOC100285495). Reverse genetic studies validated the functional importance of ZmCIPK15, causing a approximately 10° change in root angle in specific nodal positions. A steeper root growth angle improved nitrogen capture in silico and in the field. OpenSimRoot simulations predicted at 40 days of growth that this change in angle would improve nitrogen uptake by 11% and plant biomass by 4% in low nitrogen conditions. In field studies under suboptimal N availability, the cipk15 mutant with steeper growth angles had 18% greater shoot biomass and 29% greater shoot nitrogen accumulation compared to the wild type after 70 days of growth. We propose that a steeper root growth angle modulated by ZmCIPK15 will facilitate efforts to develop new crop varieties with optimal root architecture for improved performance under edaphic stress. Genome‐wide association mapping identified CBL‐interacting serine/threonine‐protein kinase 15 (ZmCIPK15) gene that controls root angle and is associated with increased deep nitrogen capture and plant performance in low nitrogen environments.